Design of a compact shielding envelope and elements of radiological protection at the TRIUMF-ARIEL facility. (May 2020) - Trudel, A.; Augusto, R.S.; Liu, Z.; Kinakin, M.; Mildenberger, J.; Gottberg, A.; Paley, W.; Minor, G.; Messenberg, A.; Bjelic, Z.; Chak, J.; Varah, S.; et al.
Abstract: The Advanced Rare Isotope Laboratory (ARIEL) is currently under construction at TRIUMF. ARIEL's mission is to supply existing experiments with more diverse and more intense radioactive ion beams (RIB) produced via the Isotope Separation On-Line (ISOL) method. The drivers inducing the nuclear reactions at ARIEL include a 500 MeV proton beam from the main cyclotron as well as a 35 MeV electron beam with the intent of simultaneous operation using two separate additional target stations. The generated RIB will be made available to experiments in condensed matter and subatomic physics as well as practical applications such as medical isotopes for life sciences research. This work details the various simulations performed using the Monte Carlo (MC) particle transport and interaction code FLUKA. The code was systematically employed to predict prompt and residual radiation levels to characterize the radiation fields generated via the irradiation of various types of targets. An iterative combined development process between CAD-based engineering of the shielding envelope, nuclear physics optimization of the target system and particle tracing simulations was established. Preliminary simulation studies resulted in the selection of shielding materials and respective thicknesses with the goal of maximizing attenuation while mitigating residual activation. The results provide clear operational constraints and aid in determination of expected dose rates outside of shielding in high occupancy areas. A series of optimization steps followed the preliminary work, testing various parameters including beam power, target material and shielding configurations. These results were evaluated considering technical feasibility, safety, and economic impacts on ARIEL construction and eventual operation. Although the project, in its infancy, is expected to proceed through stages of increasing complexity, the shielding and radiation transport modeling completed to date helps to define and validate nominal operation and failure scenario procedures for all future project stages. Highlights: Present stage of the ARIEL facility compact shielding design at TRIUMF. Monte Carlo FLUKA simulations for shielding optimization and validation. Dosimetry assessment of the ARIEL facility using FLUKA.